Noonan syndrome: cochlear implantation in the setting of cochlear nerve deficiency - Ciavarro, Giovanni; Bacciu, Andrea; Di Lella, Filippo; Vincenti, Vincenzo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Noonan syndrome (NS) is a congenital disorder characterized by a wide heterogeneity in clinical and genetic features. Hearing loss can frequently occur in NS, although not always mentioned in its diagnostic criteria. We are reporting on a child with an established NS who underwent bilateral cochlear implantation (CI) in the setting of cochlear nerve deficiency.Case presentation: We present the case of a child-girl affected by NS. Newborn hearing screening and audiological evaluations reveled an asymmetric sensorineural hearing loss (SNHL), profound at left ear and severe at right ear. Hearing aids were fitted at the age of six months. Brain magnetic resonance imaging showed hypoplastic cochlear nerves. Due to progressive worsening of the hearing thresholds and inappropriate speech development, at the age of 2 years she underwent a left-sided cochlear implantation. Four years later, right ear was also implanted. Six years after the first surgery, a partial extrusion of the electrode array was noticed. Explantation and reimplantation of a new device was performed, adopting a subtotal petrosectomy approach. The patient reached a score of 95% in open-set speech perception tests.Conclusions: Hearing loss is a frequent finding in patients with NS; however, its nature and severity are very heterogenous. In consideration of the possible progression of SNHL, audiological follow-up in NS patients must be carefully and periodically performed so as to early detect worsening of hearing threshold. If indicated, cochlear implantation should be considered, taking account of audiological and systemic features of this syndrome.